Identification of Key Patches for Biodiversity Conservation Based on Possibility of Connectivity Method - Zhang Yue; Song Bo; Liu Zaiqiang; Lei Siyu (Chemical Engineering Transactions, 2018)
Abstract: The optimization of landscape structure will benefit for biodiversity conservation by analysing the best landscape layout as the habitat patches have been rapidly lost. Based on the possibility of connectivity (PC) method have been proposed for the assessment of biodiversity value that considered both habitat size and spatial connectivity, which regards the index of PC as its primary parameter. Miyun County, Beijing is studied as a case area to evaluate the biodiversity value by both the popular method and the proposed method. It is concluded that the total biodiversity value of each concerned land use types based on 2010 dataare: grazing land 3.69×106 Yuan•ha-1•year-1, forest land 132.39×106 Yuan•ha-1•year-1, cropland 5.65×106 Yuan•ha-1•year-1, water area 18.94×106 Yuan•ha-1•year-1, built-up land 0, and unused land 0.11×106 Yuan•ha- 1•year-1. Secondly, for the identification of key patches, there are three kinds of key patches: (1) the patches with larger habitat size; (2) the satellite patches around the large patches as the undertaken area for biologicalmigration; (3) the stepping stone patches. It is found that biodiversity value is not evenly distributed with patch area because of the difference of connectivity. Larger patches and the patches locate in the connecting position are important for maintaining connectivity. The results of this paper will provide technology and data references for environmental protection in the near future.